2022
DOI: 10.1155/2022/6168284
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin Alleviates Repetitive Ketamine Exposure-Evoked Cognitive Impairment in Adolescent Mice

Abstract: Ketamine (KET) is widely used for induction and maintenance of anesthesia, and long-term use is required for treatment of depression patients. Repeated use of KET is associated with mood and memory disorders. Ulinastatin (UTI), a urinary trypsin inhibitor, has been widely undertaken as an anti-inflammatory drug and proved to have neuroprotective effects. The aim of this work was to determine whether prophylactic use of UTI could attenuate KET-induced cognitive impairment. It was found that repetitive KET anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One study reported that intravenous administration of ketamine disrupts iron homeostasis and overloads hippocampal neuronal iron in vitro and in vivo cultures, thereby contributing to the development of neurodegenerative diseases in the elderly. 40 Hong et al 41 also found that repetitive ketamine use may cause memory impairment or emotional disorders in adolescent mice.…”
Section: Discussionmentioning
confidence: 98%
“…One study reported that intravenous administration of ketamine disrupts iron homeostasis and overloads hippocampal neuronal iron in vitro and in vivo cultures, thereby contributing to the development of neurodegenerative diseases in the elderly. 40 Hong et al 41 also found that repetitive ketamine use may cause memory impairment or emotional disorders in adolescent mice.…”
Section: Discussionmentioning
confidence: 98%
“…As reported previously, ulinastatin has an excellent anti-inflammatory response, reduces the level of inflammatory mediators, relieves postoperative pain, and reduces the postoperative stress response. The clearance rate of the drug in elderly patients is slower than that in young patients, and because the kidney does not metabolize the drug, it can be used even if it the patient has impaired renal function[ 23 ]. In this study, we observed that the combination of ulinastatin and Dex could effectively reduce the stress response and improve the quality of life of patients after the operation.…”
Section: Discussionmentioning
confidence: 99%